Empowering seizure management skills: Knowledge, attitudes, and experiences of school staff trained in administering rescue drugs in Northern Italy - Bert, Fabrizio; Pompili, Erika; Gualano, Maria Rosaria; Venuti, Silvio; Minniti, Davide; Siliquini, Roberta (Epilepsy & behavior, 2021)
The administration of rescue medication at school concerns students for which it may be essential, on doctor's prescription, to take therapy during school hours. In this case, since the parents are absent, the first rescuer is necessarily the school staff, who should be properly trained because prolonged seizures can cause severe harm and even death. Every year, the Local Health Unit “TO3” in Northern Italy, provides training for school staff to administrate rescue medication at school. From December 2019 to February 2020, the same questionnaire was administered to school staff trained for seizures at the end of the course, while the staff trained for other diseases completed it before the course. About 60% of the sample (N = 123) had been trained in seizure management at least once in their lifetime. Median knowledge score in subjects with no seizures training was 7 (Q25/Q75: 5/8), while it was 9 (Q25/Q75: 6/10) in subjects with seizures training (p < 0.001). The self-reported level of confidence in their skills to administer rescue medication was high in 10.2% of subjects not trained for seizures and in 62.9% of those trained (p < 0.001). Results suggest that medical training for school staff increases knowledge scores and levels of self-confidence relating to the administration of rescue medication. Moreover, after the training, the school staff changed attitude toward seizures, no longer considering them a problem, and became more aware, less fearful, and more inclined to act in case of need, making school a better place for all students. •Results suggest that medical training for school staff boosts knowledge scores and levels of self-confidence relating to rescue medication.•After the training, the school staff changed attitude toward seizures and became more aware, less fearful and more inclined to act in case of need•Schools should be a safer place for all students